PD-1 Inhibitors Plus Capecitabine as Maintenance Therapy for Advanced Intrahepatic Cholangiocarcinoma: A Case Report and Review of Literature - Wang, Zhihong; Zeng, Tianmei; Li, Yong; Zhang, Ding; Yuan, Zhengang; Huang, Mengli; Yang, Yuan; Zhou, Weiping (Frontiers in Immunology, 2021)
Intrahepatic cholangiocarcinoma (iCCA) is the second most common primary liver cancer with a poor prognosis. Gemcitabine plus cisplatin as first-line standard of care brings an overall survival of approximately 12 months. Immunotherapy strategy represented by programmed cell death 1 (PD-1) inhibitors has been applied to the systemic treatment of advanced advanced iCCA. However, immunotherapy combined with chemotherapy as a first-line maintenance therapy were rare reported. In our report, we presented an advanced iCCA patient with a dramatic response to now over 16 months of a PD-1 inhibitor (sintilimab) combined with gemcitabine plus cisplatin as the first-line therapy and sintilimab combined with capecitabine as a maintenance therapy.